Problematika Guru dalam Program Pembiasaan Karakter Sopan Santun Siswa Sekolah Dasar Negeri 5 Kota Medan - Martha Traci Br Simanjuntak; Ayu Novita Sari Haramaito Purba; Calvin Leandro Purba; Andhika Prasetia Panjaitan; Dio Ripki Awli Ritonga; Rahmilawati Ritonga (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to describe the problems faced by teachers in the polite character habituation program at State Elementary School 5 Medan City. The method used is qualitative, with data collection through direct observation, interviews, and documentation. This research was conducted at Sekolah Dasar Negeri 5 Kota Medan, with the research subjects consisting of teachers and students. The results showed that Sekolah Dasar Negeri 5 Kota Medan has several problems faced by teachers in this program, which can be classified into three categories: (1) students' behavior that is not polite to elders, (2) student delinquency that disrupts the learning process, and (3) teacher impatience in dealing with difficult student behavior.